(untitled) (The Research of Medical Science Review, 2025)
Background: Atherosclerotic stenosis of coronary arteries is a prevalent condition often necessitating surgical intervention such as Coronary Artery Bypass Grafting (CABG). Postoperative pain, particularly at the sternotomy site, affects up to 80% of CABG patients and is associated with complications like poor pulmonary function, atelectasis, and increased morbidity. Effective postoperative pain management can enhance recovery, reduce hospital stay, and optimize resource utilization. However, conventional analgesics used in intensive care settings are frequently associated with adverse effects, necessitating the evaluation of alternative pain control strategies. Objective: To evaluate the efficacy of preoperative pregabalin in reducing postoperative pain and analgesic (including opioid) requirements, and to assess its safety profile in patients undergoing CABG surgery. Methodology: This non-randomized controlled trial was conducted at the Department of Adult Cardiac Surgery, Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi. Patients scheduled for elective CABG were allocated into two groups: one receiving a single preoperative dose of pregabalin (150 mg) and the other receiving a placebo. Postoperative pain was assessed using the Visual Analogue Scale (VAS) at rest and during deep breathing at 6, 12, 18, and 24 hours after surgery. Total postoperative opioid consumption, time to first rescue analgesia, and requirement for additional analgesics were recorded. Safety was evaluated by monitoring sedation scores and adverse events such as dizziness, somnolence, and hemodynamic changes. Results: A total of 60 patients were included, with 30 in each group. Baseline characteristics including age, gender, BMI, education, socioeconomic status, comorbidities, and surgery type were comparable between groups (p > 0.05). Postoperative pain scores were significantly lower in the pregabalin group at all time points, both at rest and during deep breathing (p < 0.01). Opioid requirements were also significantly reduced (mean 22.5 ± 4.6 mg vs. 35.8 ± 6.3 mg; p < 0.001), with fewer patients requiring rescue analgesia (26.7% vs. 63.3%; p = 0.003) and longer time to first rescue dose (10.3 ± 1.8 vs. 6.4 ± 2.1 hours; p < 0.001). Sedation scores were higher in the pregabalin group (p < 0.05), and somnolence was more frequent (30% vs. 10%; p = 0.049). No significant differences were observed in hemodynamic stability or other adverse effects. Conclusion: Preoperative administration of pregabalin is effective in reducing postoperative pain and opioid consumption in CABG patients, with an acceptable safety profile. Its use may contribute to enhanced recovery and better postoperative outcomes.